Building a Digital Transformation Strategy for Small and Medium Enterprises in Vietnam – Approaching Foresight - Nguyen Manh , Tuan; Truong Van , Tu; Le Ngoc , Thanh; Nguyen Trung , Tuan (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2023)
The study has conducted an overview of the current situation of digital transformation in small and medium enterprises (SME) in Vietnam in recent years. From the results of this review, the author has conducted a SWOT analysis to fully assess the strengths, weaknesses, opportunities, and threats of Vietnamese SMEs that are implementing digital transformation. At the same time, a Delphi survey in the direction of Foresight with more than 300 digital transformation professionals in SMEs in Vietnam to assess the characteristics and issues in the community and the future digital business vision also forecast the digital transformation needs and priority activities for implementing digital transformation in enterprises. These are considered as important steps in the process of developing a foresight strategy for SMEs in Vietnam.
Keywords: Digital transformation; SME; Digital strategy; Foresight approach